Synergistic catalytic activity of palladium–silver alloy nanoparticle for anodic oxidation of ethanol in alkali. (19th April 2021) - Chowdhury, Sreya Roy; Kanti Bera, Kamal; Ray, Apurba; Bera, Parthasarathi; Maiyalagan, T.; Bhattacharya, Swapan Kumar
Abstract: Palladium and palladium-silver alloy nano catalysts were synthesized from aqueous precursor at room temperature via a single vessel chemical reduction and co-reduction methods in absence of capping agent. XPS analysis confirms the presence of Pd and Ag in the catalyst matrix. Microscopic analyses reveal spherical morphology of the catalyst in the nanoscale dimension. The electro-analytical investigation of the catalyst loaded on carbon electrode shows that the Pd4 Ag nano alloy catalyst demonstrates marked improvement in electro-catalytic efficiency among all prepared catalysts for ethanol oxidation in alkali. The Pd4 Ag/C catalyst shows the mass normalized peak current density of 522 mA mg −1 Pd in cyclic voltammetric (CV) study, which is 1.97 times greater than that of similarly synthesized Pd/C (264.2 mA mg −1 Pd ) catalyst. Chronoamperometric and impedance analyses further establish the superiority of Pd4 Ag/C catalyst. To discover the plausible mechanism, the CV study is typically extended to the intermediates like sodium acetate which reveals that though Pd is better for catalytic oxidation of intermediate than the best catalyst but the optimal OH − adsorption on the surface of the metal, favours catalytic oxidation of ethanol more on Pd4 Ag catalyst. The mechanistic path of the reaction is anticipated by evaluating the ex-situ FTIR and chromatographic studies which explain the promotion of the formation of carboxylate in comparison to carbonate by Ag. Graphical abstract: Image 1 Highlights: Pd and Pdx Agy alloy nanoparticles are synthesized by chemical reduction method. Pd4 Ag alloy electrode show optimum synergistic catalytic activity for EOR. Plausible mechanism of EOR on Pdx Agy is proposed.